LECTURER'S COMMUNICATION ATTRACTIVENESS AND STUDENT CREATIVITY IN THAI SUMMER COURSE PROGRAM - Yulianita, Neni; Yuningsih, Ani; Wiwitan, Tresna; Susilawati, Eka; Maulana, Faisal (ann4publisher@gmail.com, 2024)
This study aims to measure and analyze facts about the relationship between the lecturer's communication attractiveness in the Summer Course program in Thailand and student creativity in the study of culture tourism. The method used is quantitative; to measure the correlation, the researcher used the Correlation Analysis Test using IBM SPSS Statistics 23 software. The results of the research show that there is a significant correlation between the lecturer's communication attractiveness, who provides learning materials on the Summer Course program at the International College RMUTK, Thailand, and the creativity of Communication Science students in West Java, Indonesia, in studying Tourism and Thai culture. In general, the conclusion of this study has proven that the communication attractiveness of lecturers consists of six variables: lecturers' communication of attractiveness, namely: taking style attractiveness, communication skill attractiveness, communication techniques attractiveness, communication strategy attractiveness, communication behavior attractiveness, communication intelligence attractiveness has a positive and significant correlation with student creativity which is measured from 9 aspects creativity, namely: setting creativity, building creativity, organizing learning, facilitate creativity, positive creativity, balance and opportunity creativity, courage and imagination creativity, managing creativity, mastery of creativity. The variable with the highest relationship value is between the variable of Lecturer Communication Appeal and variable Y: Arrangement Creativity and Building Creativity. The relationship between variables that have the lowest relationship value is between the relationship of Communication Appeal and the variable of Learning Organization. The variable of Lecturer Communication Attractiveness (X) is closely related to Student Creativity (Y).